EFFECT OF CALCIUM IONS ON THE ACTIVITY AND STABILITY OF EXTRACELLULAR LIPASE PRODUCED BY MODERATE HALOPHILIC BACTERIA HALOMONAS MERIDIANA BK-AB4 - AYU MEGGA NANDA (NIM: 10512034), GALO
Lipase is a hydrolase enzyme widely used in various industrial field, such as food, paper, detergents, and biodiesel. This study has been successfully isolated extracellular lipase produced by Halomonas meridiana BK-AB4, which is moderate halophilic bacteria that able to live in a habitate containing salt with the concentration within 0.5-22.5%. Crude extract was partially purified by the precipitation method using 30%, 60%, dan 70% of ammonium sulfate concentrations. The results of quantitative analysis showed that the highest specific activity exhibited by lipase in the fraction of 30-60%. Qualitative analysis to this fraction by SDS-PAGE, native-PAGE and zymography revealed one type of extracellular active lipase, which later be called as lipase BK-AB 4, having a molecular weight of ~50 kDa. The effect of adding various metal ions to the enzyme solution found that Ca2+ ions played role as the activator of the enzyme and the addition of EDTA decrease its activity as result lipase BK-AB4 classified as metaloenzyme. Although adding Ca2+ ions enhanced the enzyme activity in variuos pH but the optimum pH was the same at pH 8. Interestingly, the addition of Ca2+ improved the enzyme thermal stability, in which its optimum temperature shifted from 45 to 50 oC. The addition of Ca2+ ions was also enhancing residual activity towards various inhibitors, such as SDS and PMSF up to 55% and 68%, respectively. Another interesting effect of the addition of Ca2+ ions were noted when various organic solvents were added to the enzyme solution with the ration of 1:1. The activity of the enzyme was elevated up to 122% and 126% relative to the control when methanol and n-butanol were added, respectively. Further analysis of the effect of the addition of Ca2+ ions on the thermal stability of lipase showed an increase in the melting point (Tm) of the enzyme from 56 oC becomes 70 oC. The addition of Ca2+ ions also can prolong the half-life of the enzyme from 75 minutes to 85 minutes at 45 oC, which correlated with the increase of activation energy (Ea) thermal denaturation process from 3.43 kJ/mol to 3.61 kJ/mol.